2014
DOI: 10.1097/ccm.0000000000000296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bone Marrow–Derived Mononuclear Cells From Healthy or Acute Respiratory Distress Syndrome Donors on Recipient Lung-Injured Mice

Abstract: Bone marrow-derived mononuclear cells from ARDSp and ARDSexp donors showed different characteristics but were as effective as cells obtained from healthy donors in reducing inflammation and remodeling, suggesting the utility of autologous transplant of bone marrow-derived mononuclear cells in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Some studies have reported that the response to pharmacological therapies might differ depending on the primary insult [17,24,32]. The experimental models of pulmonary and extrapulmonary ARDS used herein were induced by intratracheal or intraperitoneal injection of Escherichia coli LPS, respectively, and resulted in similar degrees of lung mechanical changes at days 1 [18][19][20] and 2 [19]. In the present study, ARDSp and ARDSexp animals treated with DMSO exhibited increases in Est,L and DAD score, as well as neutrophil infiltration, compared to the C-DMSO group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have reported that the response to pharmacological therapies might differ depending on the primary insult [17,24,32]. The experimental models of pulmonary and extrapulmonary ARDS used herein were induced by intratracheal or intraperitoneal injection of Escherichia coli LPS, respectively, and resulted in similar degrees of lung mechanical changes at days 1 [18][19][20] and 2 [19]. In the present study, ARDSp and ARDSexp animals treated with DMSO exhibited increases in Est,L and DAD score, as well as neutrophil infiltration, compared to the C-DMSO group.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of LPS was selected based on previous studies demonstrating similar mechanical and morphometrical compromise in ARDSp and ARDSexp C57/BL6 mice [18][19][20]. At two time points after pre-treatment (6h and 24h), DMSO, dasatinib 1 mg/kg, or dasatinib 10 mg/ kg were given again as appropriate per group allocation.…”
Section: Animal Preparation and Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings were observed in an animal model of acute lung injury [26, 57]. As such, there may be instances in which autologous BMDMCs obtained from individuals with a given lung disease may be appropriate [26, 57]. Furthermore, it is imperative to understand which cell populations in the BMDMCs might convey beneficial effects for use in any given disease.…”
Section: Discussionmentioning
confidence: 56%